Features of diagnostics and orthodontic treatment of patients with cleft lip and palate - Фліс, П. С.; Іванова, К. В.; Циж, А. В.; Ращенко, Н. В. (Actual Dentistry, 2019)
Summary. A search and compilation of literature concerning the results of clinical trials related to orthodontic treatment of children with lip and palate clefts was conducted and summarized. Modern methods of diagnostics and treatment of this pathology were considered. Key words: orthodontics treatment, cleft palate, cleft lip.